Modelo de um sistema eutrófico: fluxo dos nutrientes e sinecologia das populações planctônicas - Patricia Benon; François Blanc; Brigitte Bourgade; Pierre Kerambrun; Michel Leveau; Pascal David; Jean Claude Romano; Dominique Sautriot; Roger Kantin (Brazilian Journal of Oceanography, 1980)
Based on the information obtained from the Gulf of Fos, France, we propose herewith a generalized model to characterize the physical, chemical and biological parameters and their interrelationship in the eutrophic coastal system. This system is characterized by having high concentration of suspended materials, especially the mineral fraction (C/N > 30). Nutrients concentrations are very high, except in diluted basins. The N-NO3/P-P04 ratio is usually low, due to the preferential assimilation of nitrates and the presence of polyphosphates from sewage waters. The concentrations of phaeopigments are always high (more than 50%), due to the mortalities of freshwater originated phytoplankton, the resuspension of dead vegetal materials, and the grazing of zooplankton. We noted in diluted water of eutrophic system the biomass is high, but the diversity is relatived low, among adapted cells with low " energetic charge". Whereas in oceanic water, the biomass is less, the diversity and energetic charge are increasing. This may indicate that phytoplankton communities have to make an effort to grow and duplicate. In comparing zooplankton populations from eutrophic to oligotrophic waters, biochemical diferentiations were observed for a same species, which may due to the difference in salinities and the presence of chemical pollutants.